2017
DOI: 10.21470/1678-9741-2017-0012
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Surgery in Jehovah's Witness Patients: Experience of a Brazilian Tertiary Hospital

Abstract: IntroductionThe outcomes of Jehovah's Witness (JW) patients submitted to open heart surgery may vary across countries and communities. The aim of this study was to describe the morbidity and mortality of JW patients undergoing cardiac surgery in a tertiary hospital center in Southern Brazil.MethodsA case-control study was conducted including all JW patients submitted to cardiac surgery from 2008 to 2016. Three consecutive surgical non-JW controls were matched to each selected JW patient. The preoperative risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(50 citation statements)
references
References 11 publications
0
50
0
Order By: Relevance
“…The study noted that there were no clinically significant differences in outcomes measured between the two cohorts, demonstrating the positive impact of EPO for patients refusing transfusion and hence supports its use for Witness patients. 8 Eleven comparative studies discussing outcomes between Witnesses and non-Witnesses were found 2,16,21,[45][46][47][48][49][50][51][52] (Table 2) and these often gave agents to increase the preoperative Hb. This varied between studies and makes comparison more challenging.…”
Section: Pre-operativementioning
confidence: 99%
See 3 more Smart Citations
“…The study noted that there were no clinically significant differences in outcomes measured between the two cohorts, demonstrating the positive impact of EPO for patients refusing transfusion and hence supports its use for Witness patients. 8 Eleven comparative studies discussing outcomes between Witnesses and non-Witnesses were found 2,16,21,[45][46][47][48][49][50][51][52] (Table 2) and these often gave agents to increase the preoperative Hb. This varied between studies and makes comparison more challenging.…”
Section: Pre-operativementioning
confidence: 99%
“…This varied between studies and makes comparison more challenging. Six of the studies reported preoperative Hb levels, [45][46][47][48]51,52 with three of these showing higher levels for the Witness group (Witness vs non-Witness: 13.7 vs 12.8 g/dL, p = 0.01; 45 13.9 vs 12.3 g/dL, p < 0.0001; 47 13.6 vs 12.9 g/ dL, p = 0.01 48 ). Similar preoperative haemoglobin levels were reported in Witness only studies (12.1 ± 1.3, 53 13.91, 8 14.1 31 and 14.5 g/dL 54 ).…”
Section: Pre-operativementioning
confidence: 99%
See 2 more Smart Citations
“…Regarding this issue, several trials have been reported, which although limited in size present valuable data. [22][23][24][25] Furthermore, many programs have revised cut-off for prescribing transfusion, based upon recommendations made by scientific societies and regulatory bodies, and meta-analyses of clinical trials. Nonetheless, it may happen that bloodless resuscitation does not suffice; in a recent survey, an Australian group have reported that 34 members of Jehovah's Witnesses suffering from major trauma bleeding, in which 3 had to undergo transfusion.…”
Section: Understanding the Refusal Of Blood Transfusion From The Jehomentioning
confidence: 99%